OPTIMASI RUTE PENDISTRIBUSIAN BBM MENGGUNAKAN ALGORITMA TABU SEARCH DAN CHEAPEST INSERTION HEURISTIC - Ulfa Is. Abdul; Muh. Rifai Katili; Djihad Wungguli (Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2023)
Distribution is an activity carried out on various types of transportation to carry out product marketing to various customers through planning by each company. In distribution, there needs to be systematic planning so as to minimize delays, one of which is the mileage factor. The purpose of this research is to optimize the optimal fuel distribution route at PT. Pertamina (Persero) Gorontalo VII Marketing Unit uses the heuristic method using the Tabu Search and Cheapest Insertion Heuristic algorithms and compares which algorithm is better which can be applied in determining the optimal fuel distribution route. The results showed that the Tabu Search algorithm was better at determining the optimal fuel distribution route with a total distance of 815.2 km, while the Cheapest Insertion Heuristic algorithm produced a total distance of 1039.7 km.